The linkage of Leadership, Psychological Empowerment, and Employee Engagement with Affective Commitment to Change: A study at public/state-owned organization. - Seta Wicaksana; Wustari L. Mangundjaya (Program Studi S3 Ilmu Manajemen, 2021)
The objective of the study is to identify the significant impact of Leadership, people’s engagement, and empowerment on affective commitment to change. The research conducted at a Public/State-Owned Organization with 539 respondents. Data was collected using employee engagement inventory, psychological empowerment, and commitment to change inventory, and was analysed using descriptive analysis and SEM. Results showed that change leadership has a significant and positive impact on affective commitment to change through employee engagement, but not through psychological empowerment. The implications of this result are beneficial for management, especially change agents. In this regard, they should create a conducive climate to develop engagement and providing many programs to increase people’s competence to establish employee commitment to change, which will be resulted in a stronger affective commitment to change.